Practice patterns of doctors of chiropractic with a pediatric diplomate: a cross-sectional survey - Long Cynthia R; Hondras Maria A; Pohlman Katherine A; Haan Andrea G (BMC, 2010)
Abstract Background Complementary and alternative medicine (CAM) is growing in popularity, especially within the pediatric population. Research on CAM practitioners and their specialties, such as pediatrics, is lacking. Within the chiropractic profession, pediatrics is one of the most recently established post-graduate specialty programs. This paper describes the demographic and practice characteristics of doctors of chiropractic with a pediatric diplomate. Methods 218 chiropractors with a pediatric diplomate were invited to complete our survey using either web-based or mailed paper survey methods. Practitioner demographics, practice characteristics, treatment procedures, referral patterns, and patient characteristics were queried with a survey created with the online survey tool, SurveyMonkey©®. Results A total of 135 chiropractors responded (62.2% response rate); they were predominantly female (74%) and white (93%). Techniques most commonly used were Diversified, Activator ®, and Thompson with the addition of cranial and extremity manipulation to their chiropractic treatments. Adjunctive therapies commonly provided to patients included recommendations for activities of daily living, corrective or therapeutic exercise, ice packcryotherapy, and nutritional counseling. Thirty eight percent of respondents' patients were private pay and 23% had private insurance that was not managed care. Pediatrics represented 31% of the survey respondents' patients. Chiropractors also reported 63% of their work time devoted to direct patient care. Health conditions reportedly treated within the pediatric population included back or neck pain, asthma, birth trauma, colic, constipation, ear infection, head or chest cold, and upper respiratory infections. Referrals made to or from these chiropractors were uncommon. Conclusions This mixed mode survey identified similarities and differences between doctors of chiropractic with a pediatric diplomate to other surveys of doctors of chiropractic, CAM professionals, and pediatric healthcare providers. The pediatric diplomate certificate was established in 1993 and provides didactic education over a 2 to 3 year span. The results of this study can be used for historical information as this specialty continues to grow.